Use of polymerase chain reaction in verification and differential diagnosis of babesiosis pathogens - Torianyk, I. I.; Tymchenko, O. M.; Ostapets, M. O.; Chygyrynska, N. A.; Pokhyl, S. I.; Kostyria, I. A.; Sorokina, I. V. (Regulatory Mechanisms in Biosystems, 2020)
Today, Babesia is recognized as one of the most common blood parasites in the world, which in terms of the number of cases of invasion is second only to trypanosomes (the causative agent of African trypanosomiasis and Chagas’ disease). These microorganisms can cause parasitism in erythrocytes and hematopoietic organs. They cause an infectious process, the clinical course of which can vary from asymptomatic, subclinical, mild or moderate influenza-like forms – to severe progressive disease (fulminant form) with fatal outcome. Thus, the latter determines the significant burden of babesia for the leading branches of medicine, veterinary medicine and the economy as a whole. The presented work is devoted to the study of the prospects for verification of babesiosis causative agents by the polymerase chain reaction (PCR) method. Blood, erythrocyte suspension, homogenized tick-carriers of babesiosis, culture of Babesia spp. were used as research material (samples). In order to obtain an objective assessment, the PCR-diagnostics method was used in two formats – standard and multiplex (multi-primer). Multiple PCR testing of multiplex format using primers in model samples containing cells of different species of Babesia (B. microti, B. divergens, B. bovis, B. canis), allowed us to establish the level of reproducibility of the results of such studies, which ranged 94.6–96.4%, to determine the level of PCR sensitivity of the multiplex format for detection/identification of human pathogenic babesia (B. microti, B. divergens and B. venatorum). It is established that the advantages of the PCR-diagnostic method of babesiosis pathogens in the samples of the studied biomaterial were: speed of research (2–4 hours); high sensitivity, specificity, reproducibility of Babesia detection results, prospects of species identification, differentiation with apicomplex spores (Plasmodium falciparum, Toxoplasma). In view of the above, the PCR method is recommended for use in cases of persistent suspicion of babesiosis infection (in cases of negative results of microscopic/cytological studies, to identify asymptomatic, subclinical and chronic forms of babesiosis, verification of active invasion in seropositive individuals and for Babesia species and their differentiation).